Version Botai legends «Er Janibek» (Eurasian Journal of Philology Science and Education, 2018)
The article analyzes the feat of Zhanibek, one of the batyrs of Abylai who lived in the 18th century. Itis known that there are several versions of the epic legend. In this article, the version of the legend of Botaiis considered. In the work the author tells about the life of the batyr from the very childhood. Particularlydetailed are two exploits with Jungars. Also, the oratorical abilities and heroic character of Zhanibek didnot remain without attention. Since this is a historical work, it describes some characteristic features ofthe genre. In general, historical legends have not been sufficiently studied. Given the genre features of thepoem, this article complements these shortcomings. The 300th anniversary of ErZhanibek was celebratedonly recently. It is known that for a long time remained a white spot and was not studied. Therefore, itis necessary to find all the variants of the epic legend and introduce it into scientific circulation. This willprovide an opportunity to learn the undiscovered pages of our history and to educate patriotism among theyounger generation. One of the main tasks is to tell the younger generation about the hero, his exploits, torevive the name of the batyr who defended his native land for the bright future of his people.